Drinking water quality variations in distribution networks – a case study at the Kumasi Water Supply System (KWSS) - Frimpong, Godfred (University of Mines and Technology, 2019)
The quality of treated drinking water at the point of use by the consumer may change after travelling through a distribution system. This study assessed changes in drinking water quality during distribution from two treatment plants at Barekese and Owabi through the Kumasi Water Supply System (KWSS). A total of 32 samples from different locations including raw and treated water from both plants, public stand-pipes, taps in homes of consumers, storage facilities, booster stations and dead-end sections of the distribution system were analysed for quality. All samples were tested using standard procedures for pH, turbidity, electrical conductivity, TDS, temperature, salinity, total hardness, calcium hardness, magnesium hardness, total alkalinity, calcium, magnesium, chloride, nitrite, residual chlorine, iron, phosphate, sulphate, manganese, ammonia, E. coli and total coliform. One-way ANOVA showed significant water quality variations during distribution for all parameters tested (p < 0.05). However, the mean values obtained for all parameters fell within World Health Organization (WHO) guidelines for drinking water quality except for E. coli and total coliform which were found to be unacceptable for some sample locations. Pearson’s Rank Correlation showed negative correlation between residual chlorine concentration and, E. coli and total coliforms. This indicates that water consumed in these communities is unsafe for consumption as there may be faecal contamination.
x, 74p; ill.
Keywords: Mining communities; Pollution; Health issues; Water quality